Financial Sustainability Ratio (FSR) Pada BUS di Indonesia Tahun 2012-2018: Penggunaan Metode Maqashid Syariah Index (MSI) - Rifka Nazilatur Rohmah; Ruslan Abdul ghofur Noor; Erike Anggraeni (Al-Tijary, 2021)
Many methods can be used in measuring company finances, including Islamic Commercial Banks. Maqashid Sharia Index (MSI) is a measuring tool in calculating the Financial Sustainability Ratio (FSR). This study aims to measure the FSR of Islamic commercial banks using the MSI measuring instrument method. The results will see the extent to which MSI can calculate the FSR of Islamic retail banks. MSI also estimates how far MSI is connected to the FSR. The method used in this research is descriptive quantitative research. The data obtained is in the form of secondary data. The data is compiled based on the financial reports of BUS that are registered with the OJK from 2012 to 2020. Sampling was done using the purposive sampling technique. The data collection technique uses the documentation method. The analysis used includes regression test, partial test, ANOVA test, and coefficient of determination. The results showed that MSI has a positive effect on FSR. MSI also provided information that the FSR provided positive results for Islamic commercial banks by being aware of the ummah's problems.